Post-cardiac arrest shock treated with veno-arterial extracorporeal membrane oxygenation: An observational study and propensity-score analysis. (January 2017) - Bougouin, Wulfran; Aissaoui, Nadia; Combes, Alain; Deye, Nicolas; Lamhaut, Lionel; Jost, Daniel; Maupain, Carole; Beganton, Frankie; Bouglé, Adrien; Karam, Nicole; Dumas, Florence; Marijon, Eloi; et al.
Abstract: Purpose: Cardiogenic shock due to post-resuscitation myocardial dysfunction is a major cause of mortality among patients hospitalized after cardiac arrest (CA). Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) has been proposed in the most severe cases but the level of evidence is very low. We assessed characteristics, outcome and prognostic factors of patients treated with VA-ECMO for post-CA shock. Methods: Using a large regional registry, we focused on all CA admitted in ICU. Among those who developed a post-CA shock, prognostic was compared according to VA-ECMO use, using logistic regression and propensity score. Specific prognostic factors were identified among VA-ECMO patients. Results: Among 2988 patients admitted after CA, 1489 developed a post-CA shock, and were included. They were mostly male (68%), with mean age 63 years (SD = 15). Fiflty-two patients (3.5%) were treated with VA-ECMO, mostly patients with ischemic cause of CA (67%). Among patients with post-CA shock, 312 (21%) were discharged alive (25% in VA-ECMO group, 21% in control group, P = 0.45). After adjustment for pre-hospital and in-hospital factors, survival did not differ among patients treated with VA-ECMO (OR for survival = 0.9, 95%CI 0.4–2.3, P = 0.84). After propensity-score matching, results were consistent. Among patients treated with VA-ECMO, initial arterial pH (OR = 1.7 per 0.1 increase, 95%CI 1.0–2.8, P = 0.04) and implantation of VA-ECMO over 24 h after ROSC (OR = 20.0, 95%CI 1.4–277.3, P = 0.03) were associated with survival. Conclusions: Post-CA shock is frequent and is associated with a high mortality rate. When used in selected patients, we observed that VA-ECMO could be an appropriate treatment.